The complete plastid genome sequence of Neopicrorhiza scrophulariiflora (Plantaginaceae): an endangered species endemic to The Himalayas regions. Issue 2 (3rd July 2019) - Zhang, Ying-Min; Qian, Zi-Gang; Zhang, Ai-Li; Yang, Cong-Wei; Li, Guo-Dong; Liu, Xiao-Li
Abstract: Neopicrorhiza scrophulariiflora (Pennell) Hong, an endangered perennial species, is endemic to the Eastern Himalayas and Hengduan Mountains. In this study, we have sequenced the complete chloroplast genome of N. scrophulariiflora, which is 152, 643 bp in length, including two inverted repeat (IR, 25, 829 bp) regions, one large single copy region (LSC) and one small single copy region (SSC) of 83, 191 bp and 17, 794 bp, respectively. The cp genome has 131 annotated genes, including 86 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The overall GC content of it is 38.1%. Phylogenetic analysis using total chloroplast genome DNA sequence of 14 species revealed that N. scrophulariiflora was closely relates to two species of Veronica with 100% bootstrap value.